1992
DOI: 10.1159/000129215
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Regeneration Capacity of Rat Liver after External Biliary Drainage

Abstract: In order to discover the effect of external biliary drainage on liver regeneration, we have produced a model system carrying cannula in the common bile duct of rat liver and examined the regeneration capacity of liver after partial hepatectomy under various conditions. Previously we have shown that hepatic cells proliferate by obstructive jaundice alone without partial hepatectomy [Terasaki et al; Jpn J Cancer Res 1991 ;82:170–175]. In the present study, we showed that DNA polymerase-α was induced by partial h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 18 publications
3
32
0
1
Order By: Relevance
“…Recently, devazepide infusion was described to exert trophic effects on the intact rat liver [14]. This was assumed to be related to cholestasis as devazepide has been shown to decrease bile secretion and bile acid output [29], and cholestasis has induced trophic effects on the liver and biliary tract [15][16][17]. Our present results confirm this hypothesis.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Recently, devazepide infusion was described to exert trophic effects on the intact rat liver [14]. This was assumed to be related to cholestasis as devazepide has been shown to decrease bile secretion and bile acid output [29], and cholestasis has induced trophic effects on the liver and biliary tract [15][16][17]. Our present results confirm this hypothesis.…”
Section: Discussionsupporting
confidence: 84%
“…Endogenous hyperCCKemia evoked in the rat by pancreaticobiliary diversion [10][11][12] or biliodigestive shunt [13] did neither influence the intact liver nor liver regeneration. Continuous infusion of CCK-8S did not exert any overt effect on the liver, whereas infusion of the CCK-A receptor antagonist devazepide induced an increased cell proliferation of both hepatocytes and bile duct epithelium in the rat [14], tentatively by a reduced bile flow [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The present study as well as the recent work [32] has proven that the external biliary drainage could not restore the impaired liver regeneration under obstructive jaundice. Pitt et al [2] showed insignificant effect of biliary decompression on the morbidity and mortality of patients with obstructive jaundice in a prospective randomized trial.…”
Section: Discussionsupporting
confidence: 38%
“…Internal biliary drainage is superior to external biliary drainage stimulating more liver regeneration demonstrated by an increased rate of hepatic DNA synthesis, liver function, liver weight, bile flow, bile salt and phospholipid secretion in the internally drained group [64][65][66] . External biliary drainage markedly suppresses regenerative capacity [67] , while with internal biliary drainage it is preserved [64] . This suggested that the bile itself contains important factors that are involved in hepatocyte regeneration, and that these factors are irreversibly removed by external drainage with adverse effects on liver regeneration.…”
Section: Biliary Drainagementioning
confidence: 99%